Development of Digital Comic Media Based on Problem Based Learning to Improve Cognitive Values ​​and Describe the Responsibility Profile of Class V Elementary Madrasah Students - Fadillah; Juarsa, Osa; Muktadir, Abdul (Jurnal Kajian Pendidikan Dasar, 2025)
This study aimed to describe the characteristics of PBL-based digital comic media, evaluate its feasibility, assess user responses, analyze students' cognitive improvement, and examine responsibility character profiles. The subjects included 24 fifth-grade students and one educator at MIM 10 Karang Anyar, Rejang Lebong. The research utilized the ADDIE model in its Research and Development (R&D) approach, encompassing Analysis, Design, Development, Implementation, and Evaluation stages. Data collection methods comprised document analysis, interviews, questionnaires, observations, and tests (pretest and posttest). Findings indicated that the media was appropriate in content, language, and design. Empirical tests showed valid, reliable, and well-differentiated questions. User responses were highly positive, with 100% teacher and 87% student satisfaction. Learning outcomes improved significantly, with a pretest score of 48.66 and posttest score of 86.72, yielding an N-Gain of 0.72 (high category). The study concluded that PBL-based digital comic media effectively enhances students' cognitive skills.